2020
DOI: 10.1111/anae.15166
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen: under or over a surgical facemask for COVID‐19 patients?

Abstract: Low-cost, easy-to-build non-invasive pressure support ventilator for under-resourced regions: open source hardware description, performance and feasibility testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 4 publications
1
24
0
Order By: Relevance
“…These findings could be explained by a decrease in room air entrainment diluting the gas mixture. 5 In contrast, Binks and colleagues 6 reported that F I O 2 , which was examined using a carbon dioxide sample line attached to a 16 G cannula, did not differ according to the position of the surgical mask relative to a Hudson oxygen mask at a flow rate of 6 L min −1 . However, the figure in their report showed significantly higher expiratory oxygen concentration when wearing an oxygen J o u r n a l P r e -p r o o f…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 94%
“…These findings could be explained by a decrease in room air entrainment diluting the gas mixture. 5 In contrast, Binks and colleagues 6 reported that F I O 2 , which was examined using a carbon dioxide sample line attached to a 16 G cannula, did not differ according to the position of the surgical mask relative to a Hudson oxygen mask at a flow rate of 6 L min −1 . However, the figure in their report showed significantly higher expiratory oxygen concentration when wearing an oxygen J o u r n a l P r e -p r o o f…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 94%
“… Gas flow to the surrounding area should be minimized as much as possible. Patients should be immediately put on a facemask with oxygen (e.g., Venturi, Hudson, or non-rebreathing masks with the lowest possible gas flow) and wear a standard surgical mask over it ( 41 ). AGP like non-invasive ventilation (NIV) or high flow nasal oxygen (HFNO) should be avoided, if possible.…”
Section: Protection Of the Patientmentioning
confidence: 99%
“…Transferring Freshly Extubated Patients Transferring extubated patients should follow the local regulations. Gas flow to the surrounding area should be minimized as much as possible by using a surgical or N95 mask over the patient's mouth ( 41 ) and nose or using a Coronavirus Safety during Intubation and Extubation (COSIE) COVID-19 Aerosol Box ( 43 ). Patients should be transferred with a facemask with oxygen if needed (e.g., Venturi, Hudson, or nonrebreather masks with the lowest possible gas flow).…”
Section: Protection Of the Patientmentioning
confidence: 99%
See 1 more Smart Citation
“…Binks et al [3] proposed placing the surgical mask directly on the patient's nose and mouth and on top of the Hudson-type mask. So, we measured and compared (Wilcoxon Rank-Sum Test) ( Supplementary Figure 1 and Table 1) FiO 2 and ETCO 2 at three different times, using a carbon dioxide sample line in two situations: First, breathing oxygen at 3 L min −1 through a Hudson-type mask with a non-rebreathing reservoir placed on, and second, under an N95 respirator; without finding differences.…”
mentioning
confidence: 99%